Initial teacher development of the Grande ABC: Institutions, vague and classes - Haas, Celia Maria (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
This research aims to organize the offer of undergraduate programs of the institutions of higher education in seven cities of Intercity Consortium Grande ABC - São Paulo - Brazil. The collection is based on the first step of the provided data offered by E-MEC, SEMESP, IBGE institutions. The first results pointed out the offer of the ABC Greater Region, fourteen undergraduate courses, and almost all of these courses have six semesters (three years) length and the majority of vacancies are given at night. We have observed some differences in the curricular proposals and a strong growth in the offer of courses in the distance education mode.